A new approach to representations of revolution - Burke, Matthew Ainslie (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 2014)
This project asserts that revolution is characterised by the expression of unthinkable possibilities, and so addresses the paradox implicit in any attempt to "write revolution." That is, how does one represent revolution without reducing it to an ordered term of reference, and thereby subduing its radical character? Additionally, can transformative action be conceptualised as a creative project to which an ethical subject may, and in fact should, be drawn? To answer these questions, my investigation develops in three strands. I combine the radical theory of Alain Badiou with similar affirmations of revolutionary intervention from Slavoj Å½iÅ¾ek and Paulo Freire, and so create an aesthetic that affirms revolutionaries as agents of supplementary creativity. My first purpose is thus to establish revolution as a productive enterprise that enables peace, rather than a destructive undertaking that introduces violence. This done, I apply the resultant conceptual tools to literary representations of radical transformation, and demonstrate that my aesthetic enables new readings of the literature of revolution to which it is applied. In the course of my analysis, I also evaluate the suitability of Badiou's ethic as a standpoint from which to engage with literature on revolution. Ultimately, then, the aesthetic I construct not only contests the notion that radical transformation is always destructive, but also renders one sensitive to revolutionary literature's excessive and supplementary dimensions.
Keywords: Radicalism in literature; Radicalism in literature -- Moral and ethical aspects; Politics and literature -- Moral and ethical aspects; Revolutionary literature, English